2018
DOI: 10.3390/s18082652
|View full text |Cite
|
Sign up to set email alerts
|

Green Communication for Tracking Heart Rate with Smartbands

Abstract: The trend of using wearables for healthcare is steeply increasing nowadays, and, consequently, in the market, there are several gadgets that measure several body features. In addition, the mixed use between smartphones and wearables has motivated research like the current one. The main goal of this work is to reduce the amount of times that a certain smartband (SB) measures the heart rate (HR) in order to save energy in communications without significantly reducing the utility of the application. This work has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Gonzálezlandero et al [2] used a smart bracelet Sony 2 for measuring heart rate and Google Fit Application Programming Interface for storing data and Android for managing data, while this study have explored the use of the smart bracelet to measure gait characteristics based on its embedded motion sensor. ese studies suggested that smart bracelets could be applied to measure several body features as health management indicators.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gonzálezlandero et al [2] used a smart bracelet Sony 2 for measuring heart rate and Google Fit Application Programming Interface for storing data and Android for managing data, while this study have explored the use of the smart bracelet to measure gait characteristics based on its embedded motion sensor. ese studies suggested that smart bracelets could be applied to measure several body features as health management indicators.…”
Section: Resultsmentioning
confidence: 99%
“…us, gait assessment was performed over 10 m. Two tapes were fixed on the start line and the finish line as markers. e instructions were given to each participant in a standard form, as follows: (1) slow: walk very slowly, as if you were walking in a park; (2) normal: walk at your normal speed to the terminal line; (3) fast: walk as fast as you can to the finish line, however, do not run or take risks. e sequence of the gait speed was randomized to avoid the effect of the order.…”
Section: Procedurementioning
confidence: 99%
See 2 more Smart Citations
“…Each person wore a smartwatch which registered, continuously, the exercise done (number of steps), heart rate, and minutes of sleep. Although these devices are not specifically medical devices, the accuracy is good enough for the input to be considered as valid, and the energy consumption requirements are becoming lower and lower [46]. Further characteristics can be found on the manufacturer's website.…”
Section: Monitoring Campaignmentioning
confidence: 99%